2023
DOI: 10.1017/s0033291723000223
|View full text |Cite
|
Sign up to set email alerts
|

Mega-analysis of association between obesity and cortical morphology in bipolar disorders: ENIGMA study in 2832 participants

Abstract: Background: Obesity is highly prevalent and disabling, especially in individuals with severe mental illness including bipolar disorders (BD). The brain is a target organ for both obesity and BD. Yet, we do not understand how cortical brain alterations in BD and obesity interact. Methods: We obtained body mass index (BMI) and MRI-derived regional cortical thickness, surface area from 1231 BD and 1601 control individuals from 13 countries within the ENIGMA-BD Working Group. We jointly mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…The ENIGMA‐BD working group brings together researchers with brain imaging and clinical data from people with BD (Hibar et al, 2016 , 2018 ; McWhinney, Abé, et al, 2021 ; McWhinney et al, 2023 ). Nineteen site members of this group from 13 countries on six continents contributed individual subject structural MRI data, medication information, and body mass index (BMI) values for a total of 2770 participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ENIGMA‐BD working group brings together researchers with brain imaging and clinical data from people with BD (Hibar et al, 2016 , 2018 ; McWhinney, Abé, et al, 2021 ; McWhinney et al, 2023 ). Nineteen site members of this group from 13 countries on six continents contributed individual subject structural MRI data, medication information, and body mass index (BMI) values for a total of 2770 participants.…”
Section: Methodsmentioning
confidence: 99%
“…These open‐source protocols are standardized across the ENIGMA consortium, and available online to foster open science, replication, and better reproducibility. They were applied in prior publications by our group (Hibar et al, 2018 ; McWhinney et al, 2023 ), and more broadly in large‐scale ENIGMA studies of major depression, schizophrenia, ADHD, OCD, PTSD, epilepsy, and autism (Thompson et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been observed in other large cohort studies using data from UK Biobank, which showed that BMI has negative correlations with CT of the bilateral entorhinal, orbitofrontal, and cingulate cortices but shows positive correlations with CT of frontal and parietal cortex ( N = 17,813) [11], and higher BMI was also related to lower GMV of various subcortical regions ( N = 9652) [12]. Furthermore, large cohort studies using data from enhancing neuroimaging genetics through meta analysis study have found that higher BMI in people with bipolar disorders indicated more pronounced CT alterations ( N = 2831) [13], and that both BMI and schizophrenia were primarily associated with changes in CT, with fewer correlates in cortical surface area (CSA; N = 3021) [14]. Moreover, obesity was significantly associated with cortical and subcortical abnormalities in major depressive disorder ( N = 6420) [15].…”
Section: Introductionmentioning
confidence: 99%
“…We have found structural brain differences between individuals with bipolar disorder and controls[69]. Further, data from the St. Göran bipolar project has been included in the Enhancing Neuro Imaging Genetics through Meta Analysis (ENIGMA) consortium, thereby contributing to large-scale collaborative brain imaging studies[70][71][72][73][74][75][76][77]}. In addition, associations between brain structure, executive function [78], and psychomotor function have been demonstrated[79, 80].…”
mentioning
confidence: 99%